2007
DOI: 10.3748/wjg.v13.i17.2504
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary sarcoidosis of liver and pancreas: A case report and review of literature

Abstract: Sarcoidosis is a chronic multisystemic granulomatous disease of unknown origin, which can involve nearly all organs. In the case of an infrequent gastrointestinal tract involvement in systemic sarcoidosis, granulomas of the liver are most commonly described while isolated pancreatic sarcoid lesions are rarely seen. We report a case of systemic sarcoidosis with exclusive extrapulmonal involvement of the liver and the pancreas in a 71-yearold white man. The diagnosis of liver involvement was confirmed by biopsy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 57 publications
(60 reference statements)
0
50
0
3
Order By: Relevance
“…17 About 10% of patients with sarcoidosis will have some form of abnormality in their transaminases or alkaline phosphatase and only about 1% will develop portal hypertension progressing to cirrhosis and liver failure. 18,19 In our group of patients with sarcoidosis, 23% had disease limited to liver only. In other studies, disease limited to liver has been reported in up to 47% of patients seen in a liver clinic.…”
Section: Discussionmentioning
confidence: 79%
“…17 About 10% of patients with sarcoidosis will have some form of abnormality in their transaminases or alkaline phosphatase and only about 1% will develop portal hypertension progressing to cirrhosis and liver failure. 18,19 In our group of patients with sarcoidosis, 23% had disease limited to liver only. In other studies, disease limited to liver has been reported in up to 47% of patients seen in a liver clinic.…”
Section: Discussionmentioning
confidence: 79%
“…However, this case highlights the fact that biliary sarcoidosis may exist in the absence of constitutional systemic symptoms, or indeed hepatic or pulmonary sarcoidosis (8). The treatment for biliary sarcoidosis is the same as for systemic sarcoidosis.…”
Section: Discussionmentioning
confidence: 84%
“…Portal hypertension with variceal bleeding, a hepatopulmonary syndrome with refractory hypoxemia, and cirrhosis leading to liver failure occur in only 1% of patients with sarcoidosis. 14 Most patients with pulmonary sarcoidosis do not require treatment. Asymptomatic CXR infiltrates are usually monitored.…”
Section: Discussionmentioning
confidence: 99%